TEACHING VOCABULARY BY USING POWERPOINT SLIDE SHOW PICTURES - Tini, Siskawati; Sada, Clarry; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The aim of this research was to solve the problemin learning English by using PowerPoint Slide Show Pictures media at the third grade elementary students of PelitaHarapan Pontianak, West Kalimantan. This study used Classroom Action Research (CAR) through 3 cycles. The participants in this study were the third grade students which consist of 38 people. The technique of data collection in this research is observation, field note and achievement test by asking students to write vocabulary based on the pictures displayed. The research finding of using PowerPoint Slide Show Pictures is the decrease number of students who get low score under Minimum Standard Completeness (KKM) of 60% in the first cycle to 5% in the last cycle. This result is categorized as moderate.It means that the students who got better score were increasing. The students also could write the words of English vocabulary with the correct spelling, they could pronounce correctly, they also could understand the meaning of words and got a lot of new English vocabulary, certainly they were really enjoyed in learning process by using PowerPoint Slide Show Pictures. Key Words: Vocabulary, PowerPoint Slide Show Picture Abstrak:PenelitianinibertujuanuntukmengatasimasalahdalammempelajaribahasaInggrismelaluipenggunaan media PowerPoint Slide Show Picturespadasiswakelas III sekolahdasarPelitaHarapan Pontianak, Kalimantan Barat. PenelitianinimenggunakanPenelitianTindakanKelas (PTK) denganmelalui 3 siklus. Adapunpartisipandalampenelitianiniadalahsiswakelas III yang berjumlah 38 orang. Teknikpengumpulan data siswamenggunakanlembarobservasi, catatanlapangandanteskemampuanyaitumemintasiswamenuliskosakatasesuaidengangambar yang telahdisajikan. Hasilpenelitianpenggunaan media PowerPoint Slide Show adalahberkurangnyajumlahsiswa yang mendapatnilairendahdibawahStandarKetuntasan Minimum (KKM) dari 60% padasikluspertamamenjadi 5% padasiklusterakhir. Hasilinimasukdalamkategori moderate. Iniberartibahwaadapeningkatanjumlahsiswa yang mendapatnilaitinggi. SiswajugadapatmenuliskosakatabahasaInggrisdenganejaan yang benar, merekadapatmelafalkansecaratepat, merekajugadapatmengertiartidari kata-kata danbanyakmendapatkankosakatabarudalambahasaInggris, dantentunyamerekasangatmenikmatidalam proses pembelajarandenganmenggunakan PowerPoint Slide Show Pictures. Kata Kunci:Kosakata, Slide Show Pictures Â